Methicillin-resistant Staphylococcus aureus nasal swabs: trends in use and association with outcomes - Hayley B. Gershengorn; Hannah Wunsch; Bhavarth Shukla (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract